PROFIL PETERNAK DAN PRODUKSI SUSU SAPI PFH LAKTASI DI DESA PANDANSARI KECAMATAN NGANTANG KABUPATEN MALANG - Bali, Vinsensius; Marhaeniyanto, Eko; Suroto, Karunia Setyowati (Fakultas Pertanian, 2017)
Research aim is to determine profile of farmers and production beef pfh lactation. The research is made as a study information and guidelines milk production beef pfh lactation to improve milk production. Research carried out in Villages Pandansari in Ngantang Malang District on 18 July to 18 August 2016. Material research is cattle farmers dairy and cattle PFH lactation were 217 tail. Methods used is the method survey (survey reseach ) with presentation of data in descriptive. The primary data was obtained from respondents used technique the questionnaire and documentation. Secondary data was a Village Administrations and KUD source prosperous Ngantang, books, the library, and literature. The sample collection in purposive sampling of farmers of dairy cattle pfh lactation by the number of 80 of 305 population based on the number of ownership of cattle and pfh lactation tail ? 2 and long ? 5 year farm. In conclusion are the education level of farmers the average primary schools with prosentase of 51.3%, farmers the average age 40 years, sex the average men of 95,0%, long as livestock the average 12 years amounting to 22.5%, scale the case of livestock assets an average of 2 tail of 32.5%, feed forage given tebon corn some 63 people or 78.8%, feed concentrates given a kind of formulation a of 100,0%, the frequency of the provision of feed forage is 3 times a day of 100,0%, the frequency of the provision of feed concentrates an average of 2 times a day of 90,0%. Milk production dairy cows in the Village Pandansari in Ngantang Malang District average is 10,72 liter/day. ujuan penelitian adalah untuk mengetahui profil peternak dan produksi sapi PFH laktasi. Manfaat penelitian adalah dijadikan sebagai bahan informasi dan pedoman kajian produksi susu sapi PFH laktasi dalam upaya meningkatkan produksi susu. Penelitian dilaksanakan di Desa Pandansari Kecamatan Ngantang Kabupaten Malang pada tanggal 18 Juli sampai 18 Agustus 2016. Materi penelitian adalah peternak sapi perah dan ternak sapi PFH laktasi. Metode yang digunakan adalah metode survey ( survey reseach ) dengan penyajian data secara deskriptif. Pengumpulan data primer diperoleh dari responden menggunakan teknik kuesioner dan dokumentasi. Data sekunder adalah dokumen pemerintah Desa dan KUD Sumber Makmur Ngantang, buku, bahan pustaka, dan literature. Pengambilan sampel secara purposive sampling dari peternak yang memelihara sapi perah PFH laktasi dengan jumlah 80 dari 305 populasi berdasarkan jumlah kepemilikan ternak sapi PFH laktasi ? 2 ekor dan lama beternak ? 5 tahun. Kesimpulannya adalah tingkat pendidikan peternak rata-rata SD dengan prosentase sebesar 51,3%, umur peternak rata-rata 40 tahun, jenis kelamin rata-rata laki-laki sebesar 95,0%, lama beternak 12 tahun sebesar 22,5%, skala kepemilikan ternak rata-rata 2 ekor sebesar 32,5%, pakan hijauan tebon jagung sebanyak 63 orang atau 78.8%, pakan konsentrat yang diberikan jenis formulasi A sebesar 100,0%, frekuensi pemberian pakan hijauan adalah 3 kali sehari sebesar 100,0%, frekuensi pemberian pakan konsentrat rata-rata 2 kali sehari sebesar 90,0%. Produksi susu sapi perah adalah 10,72 liter/hari.